The Influence of Transformational Leadership, Work Stress & Organizational Commitment on the Performance of the Ship Building Project Team at PT. PAL Indonesia Mediated by the Job Satisfaction of Project Team Members - Mochamat Adyaribowo; Tri Andjarwati; Nanis Susanti (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: PT. PAL Indonesia is a shipping industry that applies advanced technology in its operational processes. This factory is one of the best factories in Indonesia and in the Southeast Asia region. The company conducts an ongoing evaluation due to the fact that there have been delays in design & planning in the last five years. This evaluation is to find solutions to problems that occur, where the performance of employees (ship building project team) is the main concern of the Director. Design/methodology/approach: This research identifies the influence of these factors on the performance of employees (ship construction project team) of PT. PAL Indonesia. The method used is a quantitative approach where data is obtained by distributing questionnaires online to PT. PAL Indonesia. This study involved 91 respondents from employees involved in ship building projects. Then analyzed using SEM – PLS 3.3 (Structural Equation Modeling - Partial Least Square). Findings: Based on the results of the literature review, there are many factors that influence employee performance, some of which include leadership style, organizational commitment, work stress & job satisfaction. Based on the results of the SEM analysis, only 2 variables were obtained that affect the performance of the project team at PT. PAL Indonesia. The most dominant factor is in the transformational leadership variable. Practical implications: The benefits of research results can be input for companies, especially in the field of ship building. Paper type: Research paper